2012
DOI: 10.1002/bdrb.21032
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy ofGinkgo bilobaon Vaginal Estrous and Ovarian Histological Alterations for Evaluating Anti‐Implantation and Abortifacient Potentials in Albino Female Mice

Abstract: Ginkgo extract, EGb 761 is known as a vasoregulatory variable for the conventional reproduction therapy. EGb 761 was orally administered in 0 (control), 3.7, 7.4, and 14.8 mg/kg bw/day for 28 days (thereafter mated with normal fertile male), from day 1 to day 7 of pregnancy or from the 10th to 18th day of pregnancy, respectively. Vaginal smears were performed daily. On 20th day of pregnancy, the females were killed by cervical dislocation and their kidneys, liver, brain, placenta, spleen and ovaries were remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 96 publications
(99 reference statements)
0
6
0
1
Order By: Relevance
“…50 Another study examined the dose response and pathologic effects of a standardized GBE (EGb 761 ® ) in saline on cycling female Swiss albino mice. 51 The test material was orally administered at doses of 0, 3.7, 7.4, or 14.8 mg/kg body weight/d for 28 d from the day of estrus phase (prior to mating), from day 1 to day 7 of gestation, or from day 10 to day 18 of gestation. A total of 200 cycling female mice were assigned for the experiments.…”
Section: Developmental and Reproductive Toxicity (Dart) Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Another study examined the dose response and pathologic effects of a standardized GBE (EGb 761 ® ) in saline on cycling female Swiss albino mice. 51 The test material was orally administered at doses of 0, 3.7, 7.4, or 14.8 mg/kg body weight/d for 28 d from the day of estrus phase (prior to mating), from day 1 to day 7 of gestation, or from day 10 to day 18 of gestation. A total of 200 cycling female mice were assigned for the experiments.…”
Section: Developmental and Reproductive Toxicity (Dart) Studiesmentioning
confidence: 99%
“…The highest dose tested was based on the equivalent to the suggested supplement dose level for humans of three 260 mg capsules/d. 51 The effects of an aqueous GBE (similar to EGb 761 ® ) on embryo-fetal development were investigated in pregnant Wistar rats. 52 Groups of 17 rats received 0, 3.5, 7, or 14 mg/kg/ d of the test material during the tubal transit and implantation period of pregnancy.…”
Section: Developmental and Reproductive Toxicity (Dart) Studiesmentioning
confidence: 99%
“…The progesterone production was impaired by disrupting corpus luteum development that needs in early pregnancy (Elmazoudy 2018). Administration of Ginkgo biloba to female rats induces vaginal bleeding, abortion, preimplantation and postimplantation loss, and the increasing number of non-viable fetuses (Elmazoudy, 2012).…”
Section: Superovulationmentioning
confidence: 99%
“…There are no sufficient animal studies regarding reproductive toxicity, and published data are contradictory (5). For example, a study in mice showed that EGb 761 affected fertility and reproductive performance, caused vaginal bleeding, and reduced fetal viability (23,74), while a study in rats and rabbits did not show similar effects (23,75).…”
Section: Pregnancy and Lactationmentioning
confidence: 99%